2016
DOI: 10.1002/ijch.201600126
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Immobilization of Molecular Catalysts onto Carbon Nanotubes via Noncovalent Interaction for Catalytic Organic Transformations

Abstract: Since their discovery, carbon nanotubes (CNTs) continue to attract growing interest from scientists in a wide range of fields, likely due to their fascinating nanoarchitecture as well as their electronic and physical properties. From the viewpoint of synthetic chemistry, the chemical and physical stability, high surface area, and π‐stacking nature of CNTs are attractive features for their application as solid supports for molecular catalysts. The chemical functionalization of CNTs has been explored for various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 134 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…A great number of examples wherein chemically modified CNTs are used as support for metal nanoparticles (NPs) or organometallic complexes have been reported. However, non‐covalent functionalization of CNTs represents an alternative route to exploit the native properties of CNTs and a few examples regarding this approach can be found in literature . In addition, as showed above, pristine CNFs have been also exploited as nanoreactors in which confine catalyst and reagents (see below for a further example).…”
Section: Carbon Nanotubes‐based Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…A great number of examples wherein chemically modified CNTs are used as support for metal nanoparticles (NPs) or organometallic complexes have been reported. However, non‐covalent functionalization of CNTs represents an alternative route to exploit the native properties of CNTs and a few examples regarding this approach can be found in literature . In addition, as showed above, pristine CNFs have been also exploited as nanoreactors in which confine catalyst and reagents (see below for a further example).…”
Section: Carbon Nanotubes‐based Catalystsmentioning
confidence: 99%
“…However, non-covalent functionalization of CNTs represents an alternative route to exploit the native properties of CNTs and a few examples regarding this approach can be found in literature. [38] In addition, as showed above, [34] pristine CNFs have been also exploited as nanoreactors in which confine catalyst and reagents (see below for a further example). In 2007 Zhou and co-workers demonstrated that SWCNTs endowed with Pt nanoparticles and supramolecularly modified with (À)-cinchonidine (CD) were able to catalyze the asymmetric hydrogenation of ethyl pyruvate to (R)-ethyl lactate.…”
Section: Supramolecular Functionalizationmentioning
confidence: 99%
“…Carbon-based electrodes represent ideal candidates for noncovalent immobilization of metal complexes because of their high surface area, stability, and, most importantly, availability to form π−π interactions with an aryl group of the ligand framework. 68,101 Figure 6a depicts the incorporation of pyrene on an iridium pincer complex to introduce additional π−π interactions. 102 Carbon nanotubes (CNTs) are commonly used as the heterogeneous substrate; however, metal oxides are also suitable for this method.…”
Section: Noncovalent Immobilization Of Metal Complexesmentioning
confidence: 99%
“…A strategy well aligned with the green chemistry principles and which has been gaining prominence in recent years in the field of heterogeneous catalysis is the immobilization of nanoparticles (NPs) on solid supports, such as porous silica [85] , [86] , [87] , [88] , [89] , zeolites [84] , [90] , [91] , [92] , [93] , polymers [94] , [95] , [96] and carbon-based supports, including carbon nanotubes (CNTs) [97] , [98] , [99] , [100] , graphene [101] , [102] , [103] , graphene oxide (GO) [104] , [105] and graphene nanosheets (GNSs) [103] , [106] . A notable peculiarity of many of these supports – as is the case with graphene - is the property of having the surface easily modifiable, which is only possible due to the presence of large points of nucleation or stabilization [103] .…”
Section: Ultrasound-assisted Mcrs Under Heterogeneous Catalysismentioning
confidence: 99%
“…This is the case of the two procedures developed by Safari and co-workers [137] , [138] , who have designed and synthesized a hybrid catalytic system based on metallic nanoparticles incorporated in Carbon Nanotube (CNTs) or Multi Wallet Carbon Nanotubes matrices (MWCNTs). CNTs/MWCNTs are very promising support materials in heterogeneous catalysis due to their extraordinary characteristics, such as high specific surface area, excellent electron conductivity incorporated with the good chemical inertia and high oxidation stability [97] , [98] , [99] , [100] , [139] , [140] . In the first case [137] , a new nanocomposite hybrid of Pt-MWCNTs (0.93 w/w %) proved to be effective in promoting the synthesis of 2,3-dihydroquinazolin-4(1 H )-one in EtOH under ultrasound irradiation ( Scheme 8 , Table 6 , Entry 1).…”
Section: Ultrasound-assisted Mcrs Under Heterogeneous Catalysismentioning
confidence: 99%